What Use is a Critical Moment?. Issue 2 (23rd March 2020) - Laws, David
Abstract : This article takes a pragmatic approach to understanding critical moments and explores their use in three forms of practice: research, conflict diagnosis, and a form of intervention called a reconstruction clinic. Reviewing what makes critical moments useful in these practices provides insights into their character, and into how they function in the work of adept practitioners, and into the way stakeholders experience, make sense of, and act in a conflict. This review opens insights into the relationship between stories, memory, and action and into the layered and relational quality of experience that the use of critical moments helps to evoke. It also highlights a plasticity that distinguishes critical moments and helps to foster interaction and development in research, in conflict diagnosis, and in efforts to intervene in the contested history of a conflict.